Metodologias e tecnologias educacionais: possíveis abordagens para a prática pedagógica na EPT - Sousa, Benara Modesto de (Brasil, 2023)
This guide is an educational product, the result of the master’s research entitled TECHNOLOGY, EDUCATION AND WORK: perceptions and developments from Emergency Remote Teaching - ERE in the interior of the Amazon. The guide is a contribution to the organization of the integrated curriculum. The objective is to guide IFAM-TBT professors, as well as those interested in the subject, regarding pedagogical practice from the perspective of work as an educational principle, active methodologies and educational technologies in the context of Professional and Technological Education, from a critical perspective. The content of this guide correlates the concepts: work as an educational principle, pedagogical conceptions, pedagogical practice from the perspective of the Historical-Critical Pedagogical conception, Active Methodologies and Educational Technologies. During reading, there are sug gestions for texts, videos, educational technologies, etc. Finally, a glossary was created in order to present the main concepts of words and acronyms which were emphasized in the ERE.